Experimental and numerical investigation on ductile fracture mechanism of aluminium alloy using new modified model - Zhao, R.; Zhao, S.; Guo, J.; Zhong, B.; Li, J. (Materials science and technology, 2015)
In the present paper, the ductile fracture of aluminium alloy 5052P-H34 is studied by experiments and simulations. Then, the extension of the damage growth model, which captures both tension as well as shear, was employed in the present paper, and a modified Rousselier model was proposed. A stress integration algorithm based on the general backward Euler return algorithm was developed and implemented into finite element (FE) models in the ABAQUS/Explicit platform. The shear coefficient was calibrated by a FE analysis based on an inverse calibration procedure combined with the physical experiments. The predictive capability of this model was studied by comparing the experiments with the simulations, and the validity of this model was verified. The results show that the modified Rousselier model can give more accurate results for both tension and shear failure.